Measuring the Intellectual Development of College Students: Testing a Theoretical Framework - Bateman, Dianne; Donald, Janet G. (Canadian Journal of Higher Education, 1987)
The purpose of this research was to test the ability of Perry’s scheme of intellectual development to measure the intellectual development of college students. Perry’s scheme postulates four broad levels of intellectual development in the college years - dualism, multiplicity, relativity and commitment. A questionnaire was developedfrom items used in the research literature to describe thefour levels and was administered to second and fourth semester college students. Ten college instructors also participated. To test the construct validity of Perry’s scheme, different items representing a stage were examined for convergence, while the sets of items representing different stages were examined for divergence. The empirical validity of Perry’s scheme was tested by examining student responses in relation to student time in college, cumulative average and gender. The results suggest that rather than stages of development, there are two possible levels or general positions that students take toward knowledge. The first is that knowledge consists of facts and data, and that professors should supply them. The second is that knowledge is a quest in which students have responsibility for their own learning, and are expected to be able to judge the validity of arguments and to identify and defend their own point of view. More successful students had a greater tendency to adopt the second position, but the majority of the students were in agreement with statements describing the second position.